ANALISIS FUNGSI BORDA DALAM KEPUTUSAN PEMBELIAN LAPTOP (STUDI KASUS PADA SEKOLAH MENENGAH ATAS NEGERI-5 BATAM) - Rika Harman (Computer Based Information System Journal, 2015)
Decision-making will surely experienced any person anytime and anywhere, problems will arise if the decision requires some consideration because if it is not taken into account and considered it well then it will impact to the final result is bad and risky. The discussion in this study relates to the decision-making process is the decision to purchase a laptop using Borda function. Borda function known as a weighting (similar to AHP) using preference data or rank the importance of attributes (variables) to be weighted. The attributes are taken is a matter of major components, size, price, touchpad, battery, brand and operating system of a laptop. Of 7 essential attributes of a laptop will be generated each 6 preferences, so the total will be produced 42 preferences that may arise and continue to make a list of results in the form of the preference and the last was made pairwise matrix in the form of a recapitulation before drawing conclusions. Inference process itself will be done by counting the number of lines and weights that have been obtained. The highest number (the highest percentage) is the best decision to be taken as a solution. This solution will be used to help students and SMAN 5 Plot Batu Aji Lama particular grade 3 in buying a laptop.